Городища скіфського часу в Дніпровському Лівобережному Лісостепу: загальна характеристика, каталог, типологія - Білинський, О.О. (Археологія і давня історія України, 2018)
У роботі подається загальна характеристика
городищ скіфського часу на території Лівобережжя. Розглядаються причини будівництва городищ та їх конструктивні особливості, пропонується варіант типології укріплень. У кінці додається каталог відомих пам'яток. The article represents general characteristics of the
scythian time hillforts in the Dnieper left-bank forest-
steppe. The reasons of building the hillforts, history
of their investigations and existing typologies are
described. Based on the investigation of constructive
solutions which were used by scythian time population
the typology of hillforts is offered. Analysys of natural
conditions of the sites helped to construct typology of
geomorphological position of the hillforts and analysys
of the square of the sites gave the posibility to make
classification by the square. Consequently any hillfort
can be described by three main characteristics: construction, geomorphology, square. It helps to avoid subjective
assessment of hillfort functions and to separate characteristics which form the type. Settlement system
of the hillforts was analysed separately by main left Dneiper feeders. This approach allows to define a difference
in settlement system and find out a special construction solutions which were used by scythian time
population. In addition, the catalogue of the hillforts in left-bank Dnieper region is included in the article.